BLASPHEMY OF DOWRY IN INDIA AND AN INSURGENCE OF AN ARTIST: NEELIMA SHEIKH AGAINST THE SYSTEM - Hasan, Zeba (European Scientific Journal, ESJ, 2014)
The tradition of presenting gifts to the daughter by parents on the occasion of marriage initiated during Vedic societywith a feeling of love and affection and honoring the groom, this tradition later transformed into dowry system and greed and encouraged greed and malfunctioning, hence, child marriage, sati-Jauhar and restriction to girl’s education occurred in the society. During Modern period, when India became independent, the great reformers like Mahatma Gandhi, Raja Ram Mohan Roy, Ishwar ChanderVidyaSagar etc. put their tireless efforts to remove these social evils. An enactment called ‘Leti-Deti Act’was passed in 1939followed by the dowry prohibition Act 1961. In spite of all endeavors the tradition of dowry is still in vogue and at times the lust of dowry increased to such heights that in-laws of the bride ends up with offences of burning, strangulating or murdering the bride. The present research paper encompasses the origin and evolution of dowry system in India, development of this evil, malpractices of exploitations, actions taken against the immoral and criminal practice, its repercussions on contemporary society and further concludes with an insurgence of an artist ‘Neelima Sheikh’ against the sinful crime through a series of her creative art-works in which agonizing ache can be sensed. Neelima says that this is her way to pay tribute to Champa or the deceased, which is also a powerful media for influencing people in eradicating such type of wicked practices from Indian society.